CuIn1−xFexS2 – from the new metastable sphalerite to the stable chalcopyrite phase. Issue 1 (17th September 2013) - Korzun, B. V.; Pushkarev, A. V.; Zhaludkevich, A. L.; Olekhnovich, N. M.; Rusu, M.; Lux‐Steiner, M. C.
<x xml:space="preserve">Abstract</x> Stable phase CuIn1−xFexS2 (x ≤ 0.10) crystals of chalcopyrite structure were prepared by annealing synthesized CuIn1−xFexS2 material with the new quasicubic structure of sphalerite type at the high pressure of 5.5 GPa and temperatures ranging from 1170 to 1270 K. CuIn1−xFexS2 solid solutions were formed by mixing of CuInS2 and CuFe1.02S1.98 that were synthesized in advance. Phase formation in the (1 − x)CuInS2–xCuFeS2 system was investigated and the unit‐cell parameters (the lattice constants and the unit‐cell volume) were computed as a function of composition. In addition, the parameter of the tetragonal distortion (c/2a) for CuIn1−xFexS2 solid solutions of chalcopyrite structure was determined.